A Note on q-Fubini-Appell Polynomials and Related Properties - Abdulghani Muhyi; Serkan Araci (Journal of Function Spaces)
The present article is aimed at introducing and investigating a new class of q-hybrid special polynomials, namely, q-Fubini-Appell polynomials. The generating functions, series representations, and certain other significant relations and identities of this class are established. Some members of q-Fubini-Appell polynomial family are investigated, and some properties of these members are obtained. Further, the class of 3-variable q-Fubini-Appell polynomials is also introduced, and some formulae related to this class are obtained. In addition, the determinant representations for these classes are established.